أثر أبعاد القيادة التحويلية في إدارة الأزمات: دراسة استطلاعية لآراء عينة من القيادات الأكاديمية في جامعة تكريت - جاسم، أحمد عبدالكريم (جامعة تكريت - كلية الإدارة والاقتصاد, 2019)
Cares find examine the relationship and impact between two variables two major Transformational Leadership and Includes Six Sub-Variables are Charismatic Typical Impact, Stimulus Inspiring, Intellectual Arousal, Attention, Individual, Empowering Workers, The Development of University Culture, And Changing. The variable dependent University Crisis Management. Represented the questionnaire the main tool for research and distributed on a sample of (56) of University Leaders in the Tikrit University. The questionnaire consisted of two types of information: the first includes general information about the study sample. Second related variables study. Used the study a number of statistical methods for the purpose of data analysis based on statistical software (SPSS) Among the most prominent findings of the study and a positive relationship between transformational leadership and crisis management. As well as affect transformational leadership in crisis management. The most important conclusions of the study (transformational leadership academy is one of the most important models of leadership in transforming universities for the better).
تهتم الدراسة بدراسة العلاقة والأثر بين متغيرين رئيسيين هما القيادة الأكاديمية التحويلية وتضم ستة متغيرات فرعية هي التأثير النموذجي الكارزمي، التحفيز الملهم، الاستثارة الفكرية، الاهتمام الفردي، تمكين العاملين، تطوير الثقافة الجامعية، والمتغير التابع إدارة الأزمات الجامعية، ومثلت الاستبانة الأداة الرئيسية للبحث وزعت على عينة مكونة من (٥٦) من القيادات الجامعية في جامعة تكريت، وتتكون الاستبانة من نوعين من المعلومات الأولى تعريفية تضمن معلومات عامة عن عينة الدراسة، والثانية ذات علاقة بمتغيرات الدراسة، واستعملت الدراسة عدد من الوسائل الإحصائية لغرض تحليل البيانات بالاعتماد على البرنامج الإحصائي (SPSS) ومن ابرز النتائج التي توصلت اليها الدراسة وجود علاقة موجبة بين القيادة التحويلية وإدارة الأزمات وتؤثر القيادة التحويلية في إدارة الأزمات، ومن أهم الاستنتاجات التي توصلت اليها الدراسة (تعد القيادة الأكاديمية التحويلية من أكثر النماذج القيادية أهمية في تحويل الجامعات نحو الأفضل).
Keywords: القيادة التحويلية -- إدارة الأزمات -- القيادات الأكاديمية -- جامعة تكريت -- الثقافة الجامعية